2012
DOI: 10.1209/0295-5075/99/47005
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of the carrier effective masses in bulk α -PbO

Abstract: The electronic properties of an individual α-PbO layer and bulk material consisting of stacked interacting layers are studied with the first-principle calculations. It was found that while for an individual layer the top of the valence band is extremely flat, for stacked layers it becomes dispersive due to the interlayer interaction. As a result, an effective mass of holes drops from m * h = 38m0 in a single layer to m * h = 2.44m0 in bulk α-PbO. In contrast, the conduction band is almost independent of the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Corresponding disturbance can be seen in a dispersion of the 2 u and 2 d bands between Γ * and M * points. Moreover, a behavior of the host bands near the conduction band top is also altered through a suppression of the band dipping at the M * point being also controlled by the interlayer interactions of the Pb:6s 2 electrons [17]. The similar alteration in the band behavior upon substitutional doping accompanied by depletion of the electron and hole density is observed for another compound possessing the α-PbO crystal structure [21].…”
Section: The Defect-induced Local Magnetic Momentmentioning
confidence: 61%
See 1 more Smart Citation
“…Corresponding disturbance can be seen in a dispersion of the 2 u and 2 d bands between Γ * and M * points. Moreover, a behavior of the host bands near the conduction band top is also altered through a suppression of the band dipping at the M * point being also controlled by the interlayer interactions of the Pb:6s 2 electrons [17]. The similar alteration in the band behavior upon substitutional doping accompanied by depletion of the electron and hole density is observed for another compound possessing the α-PbO crystal structure [21].…”
Section: The Defect-induced Local Magnetic Momentmentioning
confidence: 61%
“…The layers within a single crystal are held together by the interlayer interaction of the Pb:6s 2 electrons [16]. In terms of the electronic properties, the interlayer interactions generate a dipping of the conduction band at M * point [17] thus inducing an effect of the band gap shrinkage. GGA tends to overestimate the interlayer separation in the layered structures, but it is also well known to underestimate the band gap size.…”
Section: Methodsmentioning
confidence: 99%
“…Now α-PbO is an indirect semiconductor having a nondegenerate dispersive conduction band at M point and a valence band consisting of six nondegenerate bands at Γ point. 17 It seems that photo-excitation with photon energy comparable to the band-gap energy can create heavy holes on the top the valence band, while higher-energy photons yield lighter holes in the deep of the valence band. Such a difference of the effective mass with the photon energy possibly leads to the photon-energy dependence of the photo-excited carrier transport.…”
Section: Resultsmentioning
confidence: 99%
“…These values differ from a previous study, which found holes 6 and 83 times heavier for bulk and monolayer PbO, respectively. 43 This difference may come from the simulation packages used. As seen in Fig.…”
Section: A Structural Vibrational and Electronicmentioning
confidence: 99%